An Innovative Academic/Practice Partnership to Support Nursing Workforce Needs and Student Clinical Education - Hahn, Judith; Resha, Cheryl-Ann; Beauvais, Audrey; Beckman, Beth; Forte, Pamela; Rebeschi, Lisa M.; Snyder, Marianne (JONA: The Journal of Nursing Administration, 2023)
Innovation is needed to solve nursing workforce issues during times of crisis. A collaborative effort between a hospital system and several universities resulted in the Bridge to Professional Practice Program that was implemented during a period of high patient volume and nursing student downtime. The program provided support for staffing needs and clinical hours to promote readiness for practice for students. The program evaluation outcomes and recommendations for improvement are addressed.
Keywords: dept.nur; peer-reviewed

Preface - Logan, Isabel; Green, Cheryl (Stabilization Approaches That Empower Clients Through Mental Health Crises, 2023)
Keywords: dept.nur; dept.swk

Use of a supplemental feeding tube device and breastfeeding at 4 weeks - Penny, F.; Brownell, E.A.; Judge, M.; Marshall-Crim, M.; Cartagena, D.; McGrath, J.M. (MCN The American Journal of Maternal/Child Nursing, 2023)
Background:Mothers having difficulty breastfeeding their infants may use alternative supportive feeding methods. Although a supplemental feeding tube device is commonly used, efficacy for supporting sustained breastfeeding remains unknown.Purpose:To describe supplemental feeding tube device use by breastfeeding mothers as an alternative feeding method through exploration of associations between supplemental feeding tube device use and continued breastfeeding at 4 weeks of infant's age.Method:Forty mothers participated. They were interviewed during the birth hospitalization and at 4 weeks postpartum. Questions addressed use of supplemental feeding tube devices, breastfeeding issues, and continued breastfeeding relationships. We examined the relationship between LATCH scores at 2 to 3 days of life.Results:Breastfeeding mothers who chose to supplement with bottle-feeding instead of use of a supplemental feeding tube device were 30% less likely to continue breastfeeding at a medium/high/exclusive level.Conclusion:Use of the supplemental feeding tube device may help avoid the potentially detrimental effect of bottle-feeding on continued breastfeeding. © 2023 Lippincott Williams and Wilkins. All rights reserved.
Keywords: Baby-friendly hospital initiative; Bottle-feeding; Breast feeding; Breastfeeding exclusive; Exclusive breastfeeding; Human milk; Lactation; dept.nur; peer-reviewed

Stabilization approaches that empower clients through mental health crises - Logan, Isabel; Green, Cheryl A. (IGI Global, 2023)
Mental health practitioners often overlook initial stabilization strategies and interventions when providing evidence-informed approaches in order to get to the so-called “important” or “interesting” part of treatment. For many mental health practitioners, the “important” or “interesting” component...
Publication Title: https://services.igi-global.com/resolvedoi/resolve.aspx?doi=10.4018/978-1-7998-8228-2
Keywords: dept.nur; dept.swk

Grow through what you go through - Ortiz, Chelsea L. (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
Being a millennial person-of-color in the twenty-first century is exhaustive in itself—adding the vulnerabilities of a global pandemic magnified that undertaking. As women, we bear the responsibilities of balancing our professional life with our family life; our role as a partner or friend with our role as an individual being; and our mental health with our social health. “Grow Through What You Go Through” explores the value of saying “Yes, I can do this too” when COVID-19 gave many a reason to say, “I’ve had enough.” Between being a supportive partner and family member to many who experienced financial and educational setbacks and being an important part of preparing the next set of future nurses to lead and excel during a global pandemic, COVID-19 enlightened my perspective on who I was at the start of COVID-19 and the person I would turn out to be by the end of it.
Keywords: COVID-19; Coping; Resilience; dept.nur

Autonomic modulation, spontaneous baroreflex sensitivity and fatigue in young men after COVID-19 - Latchman, Peter L; Yang, Qin; Morgenthaler, Diane; Kong, Lingsong; Sebagisha, J.; Melendez, Luke; Green, Cheryl A.; Bernard, Stanley; Mugno, Raymond; De Meersman, Ronald (Physiological research, 2023)
Impaired autonomic modulation and baroreflex sensitivity (BRS) have been reported during and after COVID-19. Both impairments are associated with negative cardiovascular outcomes. If these impairments were to exist undetected in young men after COVID-19, they could lead to negative cardiovascular outcomes. Fatigue is associated with autonomic dysfunction during and after COVID-19. It is unclear if fatigue can be used as an indicator of impaired autonomic modulation and BRS after COVID-19. This study aims to compare parasympathetic modulation, sympathetic modulation, and BRS between young men who had COVID-19 versus controls and to determine if fatigue is associated with impaired autonomic modulation and BRS. Parasympathetic modulation as the high-frequency power of R-R intervals (lnHFR-R), sympathetic modulation as the low-frequency power of systolic blood pressure variability (LFSBP), and BRS as the -index were measured by power spectral density analysis. These variables were compared between 20 young men who had COVID-19 and 24 controls. Independent t-tests and Mann-Whitney U tests indicated no significant difference between the COVID-19 and the control group in: lnHFR-R, P=0.20; LFSBP, P=0.11, and -index, P=0.20. Fatigue was not associated with impaired autonomic modulation or BRS. There is no difference in autonomic modulations or BRS between young men who had COVID-19 compared to controls. Fatigue did not seem to be associated with impaired autonomic modulation or impaired BRS in young men after COVID-19. Findings suggest that young men might not be at increased cardiovascular risk from COVID-19-related dysautonomia and impaired BRS.
1 citations (Crossref) [2023-10-31]
Keywords: Autonomic Nervous System; Baroreflex; Blood Pressure; COVID-19; Cardiovascular System; Heart Rate; Humans; Male; dept.hms; dept.mat; dept.nur; dept.pch; dept.ss; peer-reviewed

Integration of the Registered Nurse Care Coordinator Role in a Federally Qualified Health Center - Alicea-Planas, Jessica; Burger, Susan (The Journal of Ambulatory Care Management, 2023)
The purpose of this 1-group, retrospective case study was to analyze the expanded role of registered nurse care coordination (RNCC) on health outcomes in a primary care setting in its real-life context. The convenience sample consisted of 244 adults diagnosed with uncontrolled diabetes mellitus and/or hypertension. Secondary data entered into the electronic health record by the health care team during patient visits pre- and post-implementation of the RNCC program were analyzed. Clinical findings suggest that RNCC may provide a valuable service. Additionally, financial analysis demonstrated that the cost of the RNCC position was both self-sustaining and revenue producing.
0 citations (Crossref) [2023-10-31]
Keywords: dept.nur; peer-reviewed

A telemedicine standardized patient experience: enhancing the virtual classroom and preparing for alternative modalities of care - Maynard, Kristi; Knickerbocker, Joshua (Nursing Education Perspectives, 2023)
This pilot study explored the use of standardized patients in the virtual classroom in efforts to increase family nurse practitioner preparedness to engage in telemedicine care delivery. Using a mixed-methods approach, we determined this innovation significantly increased students' confidence in their ability to perform a telemedicine visit while also improving their satisfaction with the virtual classroom.
1 citations (Crossref) [2023-10-31]
Keywords: Delivery of Health Care; Humans; Personal Satisfaction; Pilot Projects; Students; Telemedicine; dept.nur; peer-reviewed

Social Justice Case Studies: Interdisciplinary and Non-Traditional Interdisciplinary Approaches - Green, Cheryl (Emerald Publishing Limited, 2023)
Keywords: dept.nur

Humanizing substance abuse: a theory-based educational intervention for undergraduate nursing students - Roncallo, Hannah R.; Aronson, Barbara (Journal of Addictions Nursing, 2023)
Background Healthcare providers, as well as healthcare students, have been found to harbor negative attitudes toward individuals with substance abuse disorders, impacting the care they give and subsequently creating poor patient outcomes. Purpose This study seeks to determine the effectiveness of an educational intervention, grounded in theory, toward changing nursing student attitudes regarding patients with a substance abuse disorder. Methods Nursing students participated in a teaching intervention, developed using the experiential learning theory, that utilizes modalities for each kind of learner aimed at reducing bias toward this population. The Medical Condition Regard Scale was used pre/post intervention to determine regard toward patients with the diagnosis of substance abuse. Results Student nurses maintained the least favorable attitudes toward individuals who abuse substances in comparison with patients with the diagnoses of pneumonia or gastroesophageal reflux disease; there were significant differences in attitudes toward patients who abused substances before and after participation in the educational intervention, with postparticipation attitudes being significantly more positive than attitudes before participation. Students found the educational intervention and debriefing highly satisfactory. Implications This educational intervention can provide a cost-effective, easy-to-replicate, time-efficient learning activity that could be added to undergraduate nursing curriculum.
0 citations (Crossref) [2023-10-31]
Keywords: dept.nur; peer-reviewed